First distribution records of Acetes intermedius (Decapoda: Sergestidae)from the coastal waters of Bintulu, Sarawak : population structure, length-weigh and length-length relationship. - S. M., Nurul Amin; Aziz, Arshad; Zainal, Z.; Idris, Mohd Hanafi; Siraj, Siti Shapor; Sidik Bujang, Japar (Universiti Malaysia Terengganu, 2008)
Sergestid shrimp Acetes intermedius was recorded for the first time from the Bintulu coastal waters in Sarawak. The morphological characters of the species were examined. Population structure, length-weight and length-length relationship of A. intermedius was estimated based on specimens collected from the site during February-March 2006. A total of 857 specimens (473 males and 384 females) of A. intermedius were measured for the study of size frequency structure. The mean length of the male and female was 25.6 ± 2.52 mm and 27.02 ± 3.24 mm, respectively. The sex ratio was found to be 1: 0.81 (males: females). Total length of female was on an average 1.41 mm longer than the male (P < 0.01). The equations calculated for length-weight relationship were W = 0.0025 TL3.1484 (r2 = 0.80) for male, W = 0.0033 L3.044 (r2 = 0.77) for female. The value of b for males (b = 3.148) and females (b = 3.044) were closest to 3 which was not significantly higher than isometric value (3) indicating that the growth in males and females were isometric. The estimated co efficient of correlation (r) between the total length and body weight was 0.99 for combined sexes of the species, indicating that the relationship was highly significant (P < 0.01).